An exploration of organizational climate in community-based opiate prescribing services; a mixed methods study - Kelly, Peter (My University, 2024)
Introduction: Assessing the internal dynamics of organizations has been shown to provide information that can help planners and policymakers improve service delivery. A good organizational climate, which in this study incorporates mission clarity, team cohesion, staff autonomy, communication, levels of stress, and openness to change has been shown to be of particular importance. Still, there is a dearth of evidence in this area, and while relationships between organizational factors have been identified, little is known about the mechanisms that might underpin these relationships, and there is little understanding of how to address deficits once they are identified. The objective of this study was to identify relationships between program factors that influence organizational climate and to explore which mechanisms might underpin these relationships. Methods: This paper reports on a cross-sectional, concurrent, mixed-methods study design, across twelve discrete community-based prescribing service providers (organizations) in Ireland. Data was obtained using a staff survey [n = 132] which utilized measurements of organizational readiness to change and one-to-one interviews [n = 12]. Quantitative data was analyzed using multivariate linear regression modeling which assessed relationships between variables, while interviews were analyzed using an abductive approach, both types of data were syn- thesized at the interpretation stage. Results: A range of interdependent factors were considered to affect the climate of organizations. Surveys identified that specific types of resources, such as physical infrastructure, training, and staffing resources were important for supporting a good organizational climate, while programs with greater needs had a poorer climate. Opportunities for professional growth, the skill sets of staff, and having access to e-communication were also significant. Interviewees reported that rigid organizational hierarchies and bureaucracy, philosophical views of addiction, stress, and staff turnover were influenced by the provision of fewer resources. Interdependent factors such as leadership, supervision, staff relationships, and collective training, also thought to be influenced by resources, were considered to positively influence programs. Resources were not the only challenge identified, and practices within programs and how existing resources are used were also thought to contribute both posi- tively and negatively to the internal dynamics of services. Conclusion: Key findings in this study identified that the organization of effective services is influenced by a range of specific factors, some of which can be addressed without additional resources. Overall, staff views of orga- nizations can provide us with valuable information to support service improvement. Using a mixed methods approach can not only identify where relationships between organizational variables exist but can also help us to understand the mechanisms that underpin these relationships and, importantly, how to address deficits once they are identified. In order to improve how substance misuse services work, the need for a long-term systemic approach to program development, which incorporates some of the findings from this study, is required.
Keywords: Drug policy; Organizational readiness; Treatment process outcomes; Substance use; Organizational functioning; Inclusive Society; Addiction and substance abuse; Mental health nursing; Nursing; Public health; Mental Health/Psychosocial disability; Health; Policy